2004
DOI: 10.1158/0008-5472.can-04-1691
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated CpG Oligodeoxynucleotides as a Potent Adjuvant for Inducing Type 1 Innate Immunity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 60 publications
4
92
1
Order By: Relevance
“…Two months later, mice that survived the first tumor rechallenge received a second rechallenge with 5 Â 10 4 B16OVA or B16F10 cells. Mice were sacrificed when tumor volume exceeded 1,500 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two months later, mice that survived the first tumor rechallenge received a second rechallenge with 5 Â 10 4 B16OVA or B16F10 cells. Mice were sacrificed when tumor volume exceeded 1,500 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4]. TLR9 is predominantly expressed by B cells and dendritic cells (DC) that internalize and directly respond to CpG (5).…”
Section: Introductionmentioning
confidence: 99%
“…TLR9 recognizes as ligands viral and bacterial CpG-DNA motifs, which when bound to TLR9 on macrophages and DC, causes their activation [38][39][40]. A number of studies indicate that CpG-DNA TLR9 interaction can drive a Th1 immune response, as evidenced by a Th1-dominated cytokine profile [41][42][43]. A recent report demonstrated that TLR9 played an important role in the regulation of the mycobacteriainduced Th1 responses during M. tuberculosis infection in vivo [44].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IL-12 and TNF- synergistically induces IFN- positive CTL and effective antitumor activity [34]. Moreover, IL-12 and TNF- also activate NK, NKT and Th1 cells, which also play an important role in tumor rejection [35][36][37].…”
Section: Discussionmentioning
confidence: 99%